Adaptive strategy of Stevia rebaudiana to environmental change in tropical climate based on anatomy and physiology characteristics - AHMAD DHIAUL KHULUQ; EKO WIDARYANTO; ARIFFIN ARIFFIN; ELLIS NIHAYATI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Khuluq AD, Widaryanto E, Ariffin, Nihayati E. 2022. Adaptive strategy of Stevia rebaudiana to environmental change in tropical climate based on anatomy and physiology characteristics. Biodiversitas 23: 5710-5717. High solar radiation and air temperature are the main influencing factors for plant growth and development in tropical climates. This study's objective was to understand stevia adaptation to microclimate changes at several altitudes in tropical climates. The study was conducted in a completely randomized design with altitude differences consisting of highlands, medium lands, and lowlands with ten replicates. The results showed that stevia was exposed to temperatures above 20oC during growth in the highlands by 36.46%, and in the medium lands to lowlands by 92.85%-93.96%. Meanwhile, the temperature above 30oC in the lowlands is 17.98% highest of the others. Stevia adapts to a high temperatures by increasing stomatal density, trichomes, and photosynthesis rate. Moreover, decreasing stomata (width, aperture, open percentage), leaf thickness, palisade length, xylem diameter, conductance, and transpiration rate. Stevia in the medium lands shows good adaptability with a high photosynthesis rate, percentage of open stomata 93.15%, leaf thickness 382.56 µm, and xylem diameter 30.97 µm, which is no different from the highlands. Thus, the medium lands have the potential as a new area of stevia development in a tropical climate, considering the increasingly competitive use of agricultural land in the highlands.